2017
DOI: 10.1038/ng.3894
|View full text |Cite
|
Sign up to set email alerts
|

Truncating mutations in RBM12 are associated with psychosis

Abstract: Thus far, a handful of highly penetrant mutations conferring risk of psychosis have been discovered. Here we used whole-genome sequencing and long-range phasing to investigate an Icelandic kindred containing ten individuals with psychosis (schizophrenia, schizoaffective disorder or psychotic bipolar disorder). We found that all affected individuals carry RBM12 (RNA-binding-motif protein 12) c.2377G>T (P = 2.2 × 10), a nonsense mutation that results in the production of a truncated protein lacking a predicted R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 45 publications
1
60
0
Order By: Relevance
“…Genomic studies are particularly important for idiopathic psychiatric disorders that have few proven/reproducible biological risk factors despite twinfamily studies conclusively establishing a role for inheritance 3,4 . Hopes that protein-coding variation would provide a key to schizophrenia 5,6 have not eventuated as sizable exome sequencing studies have identified only two genes to date 7,8 . In contrast, exome sequencing studies for autism identified ~100 genes with far fewer cases than for schizophrenia 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Genomic studies are particularly important for idiopathic psychiatric disorders that have few proven/reproducible biological risk factors despite twinfamily studies conclusively establishing a role for inheritance 3,4 . Hopes that protein-coding variation would provide a key to schizophrenia 5,6 have not eventuated as sizable exome sequencing studies have identified only two genes to date 7,8 . In contrast, exome sequencing studies for autism identified ~100 genes with far fewer cases than for schizophrenia 9 .…”
Section: Introductionmentioning
confidence: 99%
“…More recent whole exome sequencing (WES)/whole genome sequencing in small/modest sized multiplex families have added to the list of inherited rare protein coding variants. These include variants in previously analyzed candidate genes namely RELN (Zhou et al, 2016), UNC13B (Egawa et al, 2016), GRM5, LRP1B, and PPEF2 (Timms et al, 2013),GRIN3B (Hornig et al, 2017), SHANK2 and SMARCA1 (Homann et al, 2016), ANKK1 (Shirzad et al, 2016), RBM12 (Steinberg et al, 2017), TAAR1 (John et al, 2017), TIMP2 (John et al, 2018)and PTPRA (John et al, 2018).These insightful studies suggest the importance of such variants with large/moderate effects in disease development or in increasing the risk in the respective families with disease clustering.…”
Section: Introductionmentioning
confidence: 85%
“…SCZ cases have been repeatedly shown to carry a greater burden of large/rare CNV (>100 kb and <1%), particularly deletions affecting brainexpressed genes. Multiple rare recurrent CNV with substantial effects on risk for SCZ (genotypic relative risks [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] have been identified (e.g., 16p11.2 and 22q11.21) (5)(6)(7)(8)(9)(10). Most of these known CNV risk loci are megabase-sized and affect the dosages of many genes, but if specific genes contributing to risk could be identified it would aid our understanding of the neurobiology of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these known CNV risk loci are megabase-sized and affect the dosages of many genes, but if specific genes contributing to risk could be identified it would aid our understanding of the neurobiology of the disorder. Thus far, only a few specific genes from genetic studies of CNV and SNV have been implicated in SCZ: NRXN1 (11), TOP3B (12), RBM12 (13) and SETD1A (14), all of which provided novel insights into SCZ pathophysiology. Therefore, gene-focused CNV evaluation in large samples with high resolution capture is needed.…”
Section: Introductionmentioning
confidence: 99%